The Influence of Social Media and Trust in Institutions on Digital Participation in Indonesia - Hutajulu, Nora Lestari; Arinda Putri Lestari, Febriyani (Department of Public Administration, Parahyangan Catholic University, 2023)
The utilization of social media by state institutions holds great promise in fostering digital innovation. However, its current implementation remains limited to one-way information dissemination. Hence, this study aims to explore how social media can play a pivotal role in encouraging community digital participation, particularly concerning the adoption of digital rupiah. Additionally, it investigates the influence of institutional trust on digital participation, as higher public trust is presumed to facilitate greater engagement in digital initiatives. Employing a confirmatory quantitative approach, the research hypothesis was rigorously tested. A total of 300 responses were collected through an online survey conducted via Google Forms. These responses were subsequently subjected to analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS 3.0 tool. The study's findings indicate a substantial positive effect of social media on digital participation. However, contrary to expectations, the level of trust in institutions was not found to have a significant effect on digital participation. These results shed light on the significance of social media as a catalyst for community involvement in digital initiatives, offering valuable insights for policymakers and institutions seeking to enhance digital adoption and innovation within the community.